2005
DOI: 10.1093/ndt/gfh762
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and outcome of chronic dialysis patients admitted to an intensive care unit

Abstract: CD patients admitted to the ICU are a subgroup of patients with high mortality and SAPS II can be used to assess their probability of hospital mortality. The severity of the acute illness responsible for ICU admission and an abnormal value of serum phosphorus are determinants for ICU mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
49
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 21 publications
8
49
2
Order By: Relevance
“…Adjustment for these factors (Table 3) largely eliminated the association between ESRD status and death. Overall, our observations on mortality are congruent with those of previous studies examining the effect of ESRD in a more general ICU population (5)(6)(7)(8)(9)(10)(11)(12). These studies reported crude ICU mortality rates for ESRD ranging from 14% to 52.6%, bracketing our estimate of 22%.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Adjustment for these factors (Table 3) largely eliminated the association between ESRD status and death. Overall, our observations on mortality are congruent with those of previous studies examining the effect of ESRD in a more general ICU population (5)(6)(7)(8)(9)(10)(11)(12). These studies reported crude ICU mortality rates for ESRD ranging from 14% to 52.6%, bracketing our estimate of 22%.…”
Section: Discussionsupporting
confidence: 90%
“…From a clinical perspective, accurate estimates of prognosis would help to inform care and management of critically ill elderly dialysis patients. Several small and two large studies have described outcomes of ESRD patients admitted to the ICU (5)(6)(7)(8)(9)(10)(11)(12). ESRD status was associated with an approximately twofold higher mortality, but this effect was largely attributable to case mix and illness severity variables.…”
Section: Introductionmentioning
confidence: 99%
“…In-hospital mortality in their study was lower than in our study (34% in patients with AKI, 14% in patients with ESRD, and 9% in control subjects). Manhes et al 8 studied at 92 longterm dialysis patients who were admitted to the ICU and found mortality rates in hospital of 38%, with mean ICU LOS 6.2 Ϯ 9.9 d. Dara et al 9 examined mortality of 93 patients who had ESRD and were admitted to the ICU and found ICU, hospital, and 30-d mortality rates to be 9, 16, and 22%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…4 -6 Unfortunately, corresponding data on patients who have ESRD and are admitted to the ICU in North American centers are sparse, [7][8][9] and in toto these studies report on only 239 patients with ESRD. Only one study 7 compared in-hospital mortality in patients with ESRD (n ϭ 57), patients without ESRD (n ϭ 1219), and patients with AKI (n ϭ 254), reporting rates of 14, 9, and 34%, respectively.…”
mentioning
confidence: 99%
“…[7][8][9][10][11] The majority of past studies were small, single-center analyses with limited inference to generalize. The only previous analysis of a large regional data set used the Intensive Care National Audit and Research Centre (ICNARC) Case Mix Programme database from Great Britain.…”
mentioning
confidence: 99%